MEASURES FOR IMPROVING ACQUISITION OF PSYCHO PRODUCTIVE SKILLS IN WOODWORK TECHNOLOGY BY NCE (TECHNICAL) STUDENTS IN NORTH CENTRAL STATES OF NIGERIA - Hassan, A M; Ma’aji, S A (Sokoto Educational Review, 2011)
Adequate Acquisition of psycho-productive skills in Technology Education courses is necessary for effective and efficient teaching, learning and for self-reliance. It was observed that at woodwork technology students usually graduates from the NCE (Tech) programme without acquiring adequate psycho productive skills due to lack of provision of enough consumable materials for practice, failure to use the correct teaching methods during practical lessons, failure to render proper assistance for the acquisition of skills during attachments by students on in d u stria l work experience scheme (SIWES) and insufficient time allotted to practical lessons. Hence, this study was designed to d e te rm in e the measures that could be adopted for improved acquisition of psycho-productive skills in woodwork technology by NCE (Tech) students in Northcentral states of Nigeria. To conduct the study. ANOVA statistic was employed to test the hypothesis at 0.05 level of significance. The finding of this revealed that a total of eleven (11) teaching technique, seven (7) utilization o f educational facilities. Eight (8) SIWES operation a n d ten (1 0 )institutional factor s could be used fo r impro vin g acquisition o f psycho productive skills in woodwork technology. There was a s ig n ific a n t d iffe ren c e in the mean responses o f woodwork technology teachers in the nine tertiary institutions, on all the fifty -o n e (51) measures suggested. Based on the findings, it is recommended that the studentcentered method o f teaching (such as Demonstration technique, Assignment technique, System approach technique, Group instruction technique and others) should be used to improved acquisition o f psych-productive skills by NCE (Technical) teachers in woodwork technology.